ALASAN - ALASAN HADIRNYA RUANG PEREMPUAN SASAK DALAM TRADISI NENSEK (Sebuah Penelitian di Dusun Keloke Desa Batujai Kabupaten Lombok Tengah) - Liza Hani Saroya Wardi; Muhammad Fadjri (Journal of Innovation Research and Knowledge, 2025)
This study reveals the reasons for the presence of Sasak women's space in the nensek tradition which has been maintained from generation to generation. Departing from an inductive approach and phenomenological meaning, this study explores the experiences of Sasak women in Keloke Hamlet, Batujai Village, Praya Barat District, to understand how this space is interpreted in everyday life. The results of the study show that Sasak women's space in the Nensek tradition is not only born from economic needs or the obligation to maintain tradition, but rather is an inner space that supports, strengthens and gives meaning to their identity as Sasak women in their own hamlet. The reasons for the presence of the nensek tradition women's space in Keloke Hamlet are (1). As a medium for spiritual closeness between Sasak women and Allah SWT, (2). As a medium for strengthening self-image and Sasak cultural identity in general, (3). As a bridge for the relationship between Sasak women and their ancestors, (4). As a medium for Sasak women's creativity and increasing family economic income. Thus, Sasak women's space in the Nensek tradition is not merely a workspace but also a spiritual, historical, creative, and existential space that serves as a medium for women to forge their identity and continue their culture from generation to generation